Decoding neural circuit structure and function : cellular dissection using genetic model organisms - Celik, Arzu; Wernet, Mathias F. (Springer, 2017)
This book offers representative examples from fly and mouse models to illustrate the ongoing success of the synergistic, state-of-the-art strategy, focusing on the ways it enhances our understanding of sensory processing. The authors focus on sensory systems (vision, olfaction), which are particularly powerful models for probing the development, connectivity, and function of neural circuits, to answer this question: How do individual nerve cells functionally cooperate to guide behavioral responses? Two genetically tractable species, mice and flies, together significantly further our understanding of these processes. Current efforts focus on integrating knowledge gained from three interrelated fields of research: (1) understanding how the fates of different cell types are specified during development, (2) revealing the synaptic connections between identified cell types ("connectomics") using high-resolution three-dimensional circuit anatomy, and (3) causal testing of how iden tified circuit elements contribute to visual perception and behavior.
Keywords: Neuroanatomy.; Neural circuitry.; elektronické knihy; electronic books